2015
DOI: 10.1007/s13193-015-0436-6
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Expression in Gastric Adenocarcinoma—a Study in a Tertiary Care Centre in South India

Abstract: According to the literature available, HER2(human epidermal growth factor 2)status in gastric carcinoma has been studied worldwide, however there is a paucity of published data from India. Hence, this study was taken up to evaluate HER2 overexpression in gastric adenocarcinoma patients and to assess the relationship between its expression and clinicopathological tumor parameters. Prospective study was conducted in a teaching hospital over a period of 27 months. Total or subtotal gastrectomy resection specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…Information linking gastric tumour differentiation and HER2 overexpression have shown variable results with some studies showing an association, 24,25,26 while others have not. 20,27 The anti-HER2 antibody trastuzumab, when added to chemotherapy, improves the survival of patients with HER2 positive GGEAC. 6 Trastuzumab is available in Zambia and patients with HER2 positive breast cancers receive this treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information linking gastric tumour differentiation and HER2 overexpression have shown variable results with some studies showing an association, 24,25,26 while others have not. 20,27 The anti-HER2 antibody trastuzumab, when added to chemotherapy, improves the survival of patients with HER2 positive GGEAC. 6 Trastuzumab is available in Zambia and patients with HER2 positive breast cancers receive this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Information linking gastric tumour differentiation and HER2 overexpression have shown variable results with some studies showing an association, 24 , 25 , 26 while others have not. 20 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…Only 3+ score on IHC were considered positive in studies conducted by Halder et al, Gupta et al, Rajagopal et al and Ghosh et al [18][19][20][21] In another study conducted by Tewari et al^5, both 2+ and 3+ scores on IHC were considered positive resulting in a HER-2 positive rate of 21.4%. Among the Indian studies, FISH was performed on equivocal (IHC 2+) cases only in limited studies-Patil et al, Sunitha et al, Aditi et al and Sekaran et al [14][15][16][17] The overall HER-2 positivity described by various studies in English literature ranged between 7% and 44.2%. 14,17 The variation in prevalence rates in several studies could be attributed to the varying protocols followed for designating HER-2/neu status and the antibody used in IHC technique.…”
Section: Discussionmentioning
confidence: 99%
“…As per the studies available a wide range of HER2/ neu expression was observed in gastrointestinal adenocarcinomas. [6,7,8,9,10,11,12,13,14] In ToGA trial HER2 over expression of 3+ positivity was seen in 10.4% for resected samples. [2] For colorectal adenocarcinomas 3+ positivity on IHC was seen in 0.5 % cases.…”
Section: Discussionmentioning
confidence: 99%
“…3+ and 2+ positive cases have to be subjected to fluroscence in situ hybridization (FISH) or chromogenic insitu hybridization (CISH) for confirmation. [5,9] There is increased demand for HER2neu testing on gastrointestinal adenocarcinomas because of the survival benefit due to available targeted therapy. As many monoclonal antibodies directed against HER2 were available this can be done routinely in all gastrointestinal adenocarcinomas, not only for the targeted therapy but also as a prognostic tool.…”
Section: Discussionmentioning
confidence: 99%